Serotonin signaling modulates aging-associated metabolic network integrity in response to nutrient choice in Drosophila melanogaster - Yang Lyu; Daniel E. L. Promislow; Scott D. Pletcher (Communications Biology, 2021)
Lyu et al analysed metabolic network integrity in Drosophila melanogaster to assess the systemic effects of nutrient choice. By knocking out the serotonin receptor, 5-HT2A, they demonstrated that the effects of different macronutrients on the stability of metabolic networks is mediated through serotonin signalling.